Letter (copy) - McDonald, Florence
026-0137-001 Secretary's. FEM/KMS/210. 23rd March, 1939. Senor Luis Araquistain, 1, rue Lord Byron, PARIS. Dear Sir, I have received your letter of the 20th March, addressed to Sir WaIter Citrine, in which you say that your wife and yourself are thinking of fixing your residence in London. I note that you would like to use the name of Sir Walter as a reference in applying to the Immigration Officiers for an English visa. I regret, however, that Sir Walter Citrine is in the West Indies serving with the Royal Commission. In case of urgency perhaps you know someone else in the Labour Movement who could give you the necessary recommendation. Otherwise I am afraid I shall have to keep your letter until Sir Walter returns, which may be some few weeks. Yours truly, Private Secretary. 292/946/26/137